2010
DOI: 10.1007/s11307-010-0374-1
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTA-NOC PET/CT Imaging of Neuroendocrine Tumors: Comparison with 111In-DTPA-Octreotide (OctreoScan®)

Abstract: Although ⁶⁸Ga-DOTA-NOC and OCT images were similar, in this study, ⁶⁸Ga-DOTA-NOC demonstrated more true positive tumor foci and was better tolerated by patients. This direct comparison supports replacement of OCT with ⁶⁸Ga-DOTA-NOC-PET/CT in the evaluation of NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 19 publications
1
79
0
3
Order By: Relevance
“…It seems explicable that such a discrepancy in results is related to the use of hybrid PET/CT imaging in 68 Ga-DOTATATE, 68 Ga-DOTATATE PET/CT fusion image showed uptake in the aortocaval soft tissue mass (SUVmax 6.7) but 18 F-FDG PET/ CT fusion image showed no FDG avidity (arrow). The lesion was later confirmed to be metastasis on resection which provides better spatial resolution and image quality, leading to higher lesional detectability compared to conventional gamma imaging with 111 In-octreotide [38,39] Ga-DOTATA TE expectably contributes the most (Fig. 3).…”
Section: F-fdg Pet/ct Images Although 68mentioning
confidence: 99%
“…It seems explicable that such a discrepancy in results is related to the use of hybrid PET/CT imaging in 68 Ga-DOTATATE, 68 Ga-DOTATATE PET/CT fusion image showed uptake in the aortocaval soft tissue mass (SUVmax 6.7) but 18 F-FDG PET/ CT fusion image showed no FDG avidity (arrow). The lesion was later confirmed to be metastasis on resection which provides better spatial resolution and image quality, leading to higher lesional detectability compared to conventional gamma imaging with 111 In-octreotide [38,39] Ga-DOTATA TE expectably contributes the most (Fig. 3).…”
Section: F-fdg Pet/ct Images Although 68mentioning
confidence: 99%
“…Compared with our study in which we found a higher percentage of additional lesions (50%), it seems we could have a better detection rate. Moreover, 64 Cu-DOTATATE found several lesions not detected on CT scans, which is less commonly reported for the 68 Ga-labeled tracers (32,34,35), which could easily be explained by the better resolution obtained when using 64 Cu than 68 Ga due to the 4-fold-lower positron range of 64 Cu. Moreover, in contrast to our study with 64 Cu, most of the 68 Ga studies did not rigorously perform a long-term follow-up to establish whether the additional foci were true-positive.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, such comparative studies also found more foci identified with 68 Ga-based tracers than with SPECT (27,31,32). These studies on average found 30% (27,32,33) more foci using PET than SPECT. Compared with our study in which we found a higher percentage of additional lesions (50%), it seems we could have a better detection rate.…”
Section: Discussionmentioning
confidence: 86%
“…Although it appears to have a lower detection rate for malignant PCCs/PGLs than I 123 MIBG [103], a high sensitivity has been reported in head and neck PCCs/PGLs [104]. Recent reports on the use of positron-emitting 68Ga-labeled somatostatin analogues (DOTATOC, DOTATATE, or DOTANOC) show higher sensitivity for PCC/PGL detection than indium-111 due to higher affinity and superior resolution of PET [105,106]. Reports of small series to date also indicate that Ga-68 DOTATATE imaging may be superior to I 123 MIBG in the diagnosis and staging of metastatic PCCs/PGLs [107,108].…”
Section: Somatostatin Receptor Imagingmentioning
confidence: 99%